floating criminal elements; Feasibility of investigating the elements of environmental crimes - Sahar Hajibeigi; Hasan Alipour; Batool Pakzad (مطالعات فقه و حقوق اسلامی)
The floating of the element of the criminal result is related to the floating and dynamism of the subject of the crime as well as the criminal behavior, and although the feature of floating is crystallized in the element of the result, in general, the constituent elements of environmental crimes will have the characteristic of floating. The present article, using library sources and descriptive analytical method, by examining the link between the three elements that make up the material element of environmental crimes and focusing on the result element, has reached the achievement that in these crimes, after investigating the behavior of the perpetrator, the elements Criminals are constantly changing; Therefore, the way they are recognized by the relevant environmental authorities and the way of their judicial verification, requires continuous monitoring and multiple evaluation. This attitude provides a dynamic and differential criminal policy that is in line with other measures and policies to protect the environment at a time when crimes against it are committed abundantly by governments and legal and natural persons. It is necessary.